Training Needs Assessment and Human Resources Skills Development: A Field Study at the Saidal Factory, Framal Branch in Annaba - Bounakhla, Farid (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
This study aims to explore the relationship between training needs assessment and human resources skills development at the Saidal Pharmaceutical Factory, Annaba branch. With the increasing focus on technology, knowledge-based economies, digitalization, and artificial intelligence, organizations are progressively adopting these technologies across various departments. As a result, significant budgets have been allocated for the training process to adapt to these new changes. This shift has led to a greater emphasis on enhancing and developing the skills and capabilities of the workforce, which today is the main driver of creativity, innovation, and competitive advantage. In this study, we relied on key methodological techniques such as observation, interviews, and surveys, applying them to a group of respondents. We reached several conclusions, the most important of which is that the relationship between training needs assessment and human resources skills development forms an integral part of achieving organizational excellence by prioritizing targeted training initiatives needed by organizations. Effective training needs assessment fosters a culture of continuous learning and development, empowering employees to take responsibility for their professional growth. This proactive approach not only enhances individual capabilities, but also enhances creativity and adaptability within teams, ensuring that the organization is able to respond quickly to economic changes and new technologies.